Concentrations of polychlorinated biphenyls and toxic metals in short-tailed shearwaters following a mass mortality event - Eliza Hamilton; Richard B. Banati; Thomas E. Lockwood; David P. Bishop (Marine Pollution Bulletin, 2026)

Riparian restoration benefits across space and time in subtropical Australia: From drinking water quality to wider society - Joseph M. McMahon; James C.R. Smart; Ben Stewart-Koster; Syezlin Hasan; James S. Shortle; William N. Venables; Andrew Smolders; Morag Stewart; Don Butler; Jon M. Olley; David P. Hamilton; Stuart Bunn (Ecosystem Services, 2026)

Benzalkonium chloride adaptation induces filamentation in Listeria monocytogenes HL06 and enhances its growth in pasteurized milk and pork sausage at 4 °C - Tao Yu; Xiaojie Jiang; Xiaobo Xu; Hongxia Zhu; David P. Hamilton; Shuxing Qiu; Junlei Yin; Xiaobing Jiang (Food Microbiology, 2026)

Cyanobacterial dominance responds nonlinearly to phosphorus additions under nitrogen enrichment in microcosms from a large drinking water reservoir - Man Xiao; Haiming Kan; Michele A. Burford; David P. Hamilton; Bao Qian; Lian Peng; Yuying Li; Hai Xu; Dawei Wang; Guangwei Zhu (Hydrobiologia, 2026)

Scanning the horizon for harmful cyanobacterial blooms - Xuexiu Chang; Hugh J. MacIsaac; Ingrid Chorus; George S. Bullerjahn; Rainer Kurmayer; Chi-Yong Ahn; Xiangzhen Kong; Steven W. Wilhelm; Susanna A. Wood; Xiangming Tang; Hans W. Paerl; Sabine Hilt; et al. (Trends in Ecology & Evolution, 2026)

What triggered the catastrophic 15 January 2022 Hunga eruption? - Jie Wu; Shane J. Cronin; Marco Brenna; Joali Paredes-Mariño; Sung-Hyun Park; Mila Huebsch; Alessio Pontesilli; Chris Firth; David Adams; Teresa Ubide; Kyle Hamilton; Alice MacDonald; et al. (Earth and Planetary Science Letters, 2026)

A cautionary tale of disequilibria in microlite-melt evolution driven by fast crystallization kinetics: Implications for modeling volcanic processes - Jie Wu; Alessio Pontesilli; Marco Brenna; Shane J. Cronin; Sung-Hyun Park; Joali Paredes-Mariño; Kyle Hamilton; Marta Ribó; David Adams; Mila Huebsch (Earth and Planetary Science Letters, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Source-specific carbon dioxide production and acetoclastic methanogenesis upon anaerobic degradation of dissolved organic matter - Yongqiang Zhou; Jiayi Wu; Lei Zhou; Yunlin Zhang; Kyoung-Soon Jang; Liwei Zhang; José R. Paranaíba; Christopher C. Keneally; Justin D. Brookes; David P. Hamilton; Erik Jeppesen (Geochimica et Cosmochimica Acta, 2026)

Finding needles in a haystack: measuring ambient concentrations of naturally occurring elongated mineral particles in an urban environment - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Wenxia (Wendy) Fan; Araliya de Zoysa; Cindy Z. Yi; Paul G. Young; Ayrton Hamilton; Nick Talbot; Martin Brook; Brett Wells; David E. Williams; et al. (Chemosphere, 2026)

Regulation of venom composition by the Australian funnel-web spider Hadronyche infensa is achieved via compartmentalised toxin production and venom metering - David Morgenstern; Brett Hamilton; Darren Korbie; Karl R. Clauser; Brian J. Haas; Greg Bowlay; Kjetil L. Voje; Alun Jones; Deon J. Venter; Glenn F. King; Eivind A.B. Undheim (Toxicon, 2026)

Hysteresis during storm events impacts stream sediment and nutrient load calculations - Donghwan Kim; Melanie E. Roberts; Jing Lu; David N. Orr; David P. Hamilton (Journal of Hydrology, 2026)

Opportunities for remote sensing to monitor freshwater water quality after extreme weather events: A systematic review - Jiatan Liang; Andres Felipe Suárez-Castro; Tim Malthus; David P. Hamilton (Journal of Hydrology, 2026)

Antimicrobial resistance genes in biosolid-amended pasture soils: Insights from a pilot study on a sheep farm - Nuno Silva; Xinyi Huang; Rachael Duncan; Carol Currie; Scott Hamilton; Sophie Lawson; Emily Robertshaw-McFarlane; Eleanor Watson; George King; David A. Ewing; Sarah Brocklehurst; Ruth N. Zadoks; et al. (Journal of Environmental Management, 2026)

Laryngectomy Education and Training Resources: An Environmental Scan of Resources - Laura-Jayne Watson; Emer Fahy; David W. Hamilton; Linda Sharp; Vicky Thornton; Joanne M. Patterson (Journal of Cancer Education, 2026)
In many settings, head and neck cancer (HNC) services are centralized in large hospitals, meaning that community input from HNC specialists can be lacking. Community healthcare professionals often require laryngectomy-specific education and training to provide optimal care to people at home. However, laryngectomy-specific education/training is often sporadic and varies between centres, making it difficult to achieve standardisation in healthcare professionals’ laryngectomy knowledge and skills. This study aimed to identify and critically review existing laryngectomy education/training resources for healthcare professionals, which include elements applicable to community care. We used environmental scanning to systematically and comprehensively identify and examine all available education/training resources which had an element of education and/or training applicable to community laryngectomy care. Eligible resources were reviewed for training-specific details, laryngectomy-specific details, evaluation method, accessibility, and patient and public involvement (PPI). A total of 6655 resources were screened; 49 were eligible for data extraction. There was wide variability in the level of laryngectomy-specific content in the resources. PPI in development was lacking, and data detailing the impact of resources on healthcare professionals’ knowledge/skills and patient outcomes was sparse. This is the first study to systematically identify and appraise laryngectomy education/training resources which have applicability to community care. There is not one consistent approach to education/training development method, content, delivery, or evaluation, likely rendering these ineffective and lacking impact. Community-specific laryngectomy education and training, with clear implementation and evaluation, is required.

Nitrogen fixation is driven by cellular nitrogen stores in a diazotrophic cyanobacterium: Evidence from culture experiments and model validation - Man Xiao; Michele A. Burford; Marieke A. Frassl; Anusuya Willis; Melanie E. Roberts; David P. Hamilton (Limnology and Oceanography, 2026)
Diazotrophic cyanobacteria, including those responsible for harmful algal blooms, fix atmospheric dinitrogen (N 2 ) to sustain growth when they are limited by dissolved inorganic nitrogen (DIN) supply. Conventional models fail to accurately predict the timing and magnitude of N 2 fixation, partly because of oversimplified assumptions about diazotrophic species responses to N. We hypothesized that cellular carbon (C) and N would co‐vary with DIN availability, and cellular N quota reduced below a critical threshold would trigger heterocyst differentiation and N 2 fixation. Conversely, we hypothesized that heterocysts would be discarded, and N 2 fixation would cease at another higher cellular N quota threshold. To test this hypothesis, we undertook experiments to provide data to calibrate a model of cellular C and N of N 2 fixation in the cyanobacterium Raphidiopsis raciborskii . The model incorporated internal N quotas, external DIN supply and a time lag for N 2 fixation as key regulators of heterocyst production and N 2 fixation, explaining > 70% of the variation in measured cellular N and C : N molar ratios. Heterocysts were predicted to form at a cellular N quota of 0.085 mg N mg −1 C and were discarded from filaments at 0.275 mg N mg −1 C. There was a 5‐d time lag between DIN deprivation and initiation of N 2 fixation. Continuous DIN supply was predicted to enhance N 2 fixation more than an equivalent one‐off pulse. Our study highlighted the need to consider cellular N and N supply regimes in driving N 2 fixation to provide more accurate predictions of the response of cyanobacteria to DIN availability.

Embracing Holistic Formulation Strategies to Maximise Positive Outcomes in Aquaculture Nutrition - Artur N. Rombenso; Brett D. Glencross; Kyla Zatti; Helen Ann Hamilton; Luiz H. David; Ha H. Truong; Cedric J. Simon (Reviews in Aquaculture, 2026)

Hypolimnetic Nutrient Subsidies to Surface Waters of a Large Lake: A Coupled Hydrodynamic Modelling and Nitrogen Isotope Field Assessment - Simon D. Stewart; David P. Hamilton; W. Troy Baisden; Piet Verburg; Kohji Muraoka; Derek C. Roberts; Brendan J. Hicks; Ian C. Duggan; Nico Donovan-Pereira (Ecosystems, 2025)
Upwelling of hypolimnetic water in lakes is important for littoral food webs as it enhances production through nutrient subsidies to surface waters. The aim of this study was to understand the role of hypolimnetic upwelling on littoral nutrient supply and diet of a freshwater unionid mussel, kākahi ( Echyridella menziesii) in an oligotrophic lake using stable isotopes (δ 15 N) as a tracer of hypolimnetic nitrogen. Upwelling events can be highly variable spatially and temporally, so to complement observations, this study used a three-dimensional hydrodynamic model (AEM3D) to simulate the transport of water from upwelling events and understand their potential impacts on kākahi. The study was conducted over an annual cycle in a large (area 620 km 2 , average depth ~ 94 m), monomictic, oligotrophic New Zealand lake. The hydrodynamic model simulations showed a strong spatial gradient. Upwelling was strongest along north-facing areas of the western shoreline owing to the prevailing south-westerly winds. The spatio-temporal distribution of nitrate-δ 15 N within the littoral zone was positively related to the rate of simulated upwelling, indicating inputs of 15 N-enriched hypolimnetic water. Kākahi δ 15 N values were positively related to upwelling averaged over an annual period, demonstrating that upwelling hotspots are ecologically meaningful. Interestingly, littoral particulate organic matter δ 15 N showed no pattern with upwelling but were homogeneous in distribution, consistent with rapid flushing with offshore water. These findings suggest that benthic littoral habitats act as hotspots for nutrient subsidies to surface waters, and that the signature of 15 N is retained over periods far longer than the duration of the upwelling by cycling within benthic primary producers and consumers.

A novel approach for quantifying elongated airborne mineral particles (EMPs) using an automated scanning electron microscope (SEM) - Anushka Elangasinghe; Hamesh Patel; Kim N. Dirks; Ayrton Hamilton; Wenxia (Wendy) Fan; Shuoyu Chen; Nick Talbot; Shanon Lim; Jed Januch; Martin Brook; Brett Wells; David E. Williams; et al. (Atmospheric Environment, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

Changes in hydrodynamics and water quality of a subtropical meromictic urban lake - Hengyu Wei; Hong Zhang; David P. Hamilton; Fuxin Zhang; Steven McVeigh (Environmental Monitoring and Assessment, 2025)
Coastal canal and waterway development has expanded rapidly over the past half-century, contributing to environmental issues such as declining water quality and saltwater intrusion. This study analysed 35 years of field sampling data from a subtropical meromictic lake to investigate water quality changes caused by intermittent saltwater intrusion. Saltwater intrusion began after a canal expansion converted a stormwater pipe into a bidirectional conduit, allowing saltwater to flow into the lake during high tides. Lake surface water temperature increased at a rate of 0.019 °C p.a. and pH has shifted from acidic to circumneutral over the study period, likely due to the disturbance of a pyrite layer during the initial construction phase and progressive increases in trophic state. Salinity accumulation in the bottom waters has caused the lake to transition from monomictic to meromictic, with stratification increasing through the 1990s, as evidenced by increases in Schmidt stability index. This shift to meromixis has resulted in permanent bottom-water deoxygenation and has led to eutrophication, evidenced by elevated nutrient levels and the development of a deep chlorophyll layer at the chemocline of the lake within recent years. This study provides valuable insights for managing other coastal lakes and wetlands experiencing similar challenges, offering guidance on mitigating the adverse impacts of saltwater intrusion that may increase with sea level rise due to climate change.

Impacts of changes in climate and water demand on flow in a subtropical river catchment below a major dam - Chao Deng; Hong Zhang; David P. Hamilton; Anna Hollingsworth (Journal of Environmental Management, 2025)

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Ultimate Fighting Crab: Agonistic Behaviour, Dominance, and Recognition in the Edible Crab, Cancer pagurus (L.) - Finlay James Archibald Hamilton; Jonathan David Wilkes; Kevin Scott (Fishes, 2024)
Edible crabs (Cancer pagurus) are an economically important species for Scottish inshore fisheries, with an estimated annual landing value of GBP 16 million (2023). Research into the behaviour, particularly agonistic behaviour, of this species is currently lacking. This paper aims to investigate behaviour, social interactions, potential hierarchies, and the impact of claw size on the outcomes of agonistic interactions of male C. pagurus through behavioural trials and retrials. Crabs were semi-randomly assigned to pairs (based on allocated condition index rating) and introduced to one another in trial tanks. Each pair underwent two trials, 24 h apart (the “trial” and “retrial”). Analyses of video records of agonistic bouts revealed that 77% of retrials were won by the initial victors, with a significant decrease in fight time between trials and retrials. Fight time was not correlated with weapon size (claw length, height, and depth). There were no differences in weapon size of winners and losers of bouts. Winners exhibited a significantly higher frequency of aggressive and dominant behaviours (approach, aggressive contact, threat displays, and mounting), and losers exhibited higher frequencies of submissive behaviours (withdrawal, retracting limbs, and remaining motionless). These results suggest that individual behaviour may play more of a role in dominance than size or other morphometric characteristics.

Mercury speciation in environmental samples associated with artisanal small-scale gold mines using a novel solid-phase extraction approach to sample collection and preservation - David King; Michael Watts; Elliott Hamilton; Robert Mortimer; Michael Coffey; Odipo Osano; Marcello Di Bonito (Environmental Geochemistry and Health, 2024)
In artisanal small-scale gold mines (ASGM), mercury (Hg) is known to pollute nearby river waters and sediments where it can be methylated to the highly bioavailable methylmercury (MeHg). The assessment of Hg speciation in water samples has been challenging for many years, with recommended procedures often not adequately allowing for analysis of samples in a suitable timeframe. Using a novel solid-phase extraction (SPE) method for sampling and preservation of Hg species, representative speciation data can be safely and easily collected and retained for up to 4-weeks (MeHg = 115 ± 8% refrigerated and 109 ± 13% unrefrigerated storage; Hg 2+ = 100 ± 14% refrigerated and 94 ± 12% unrefrigerated storage). Concentrations of MeHg in environmental water samples and drinking water were below detection limit across two ASGM sites in western Kenya and concentrations of Hg 2+ were below drinking water guidelines; however, drinking water sources contribute 20–30% of the tolerable weekly intake of Hg, indicating a need to minimise exposure of Hg from dietary sources to prevent Hg poisoning. Sediments from receiving rivers at ASGM sites showed total Hg concentrations above guideline limits (0.08–1.84 mg kg −1 total Hg) along the length of the river; however, MeHg concentrations fluctuated dependent on the stagnation of the river due to damns and ponds (5.9 ± 14.3 µg kg −1 MeHg). The findings show that SPE can be used as a robust sample collection and preservation approach for Hg speciation, which can better inform mitigation measures, understand ecological and human health implications, and improve environmental monitoring.

Individual-based modelling of adaptive physiological traits of cyanobacteria: Responses to light history - Mohammad Hassan Ranjbar; David P. Hamilton; Michael L. Pace; Amir Etemad-Shahidi; Cayelan C. Carey; Fernanda Helfer (Ecological Modelling, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Migration of transition metals and potential for carbon mineralization during acid leaching of processed kimberlite from Venetia diamond mine, South Africa - Baolin Wang; Nina Zeyen; Sasha Wilson; Makoto J. Honda-McNeil; Jessica L. Hamilton; Konstantin Von Gunten; Daniel S. Alessi; Thomas R. Jones; David J. Paterson; Gordon Southam (Applied Geochemistry, 2024)

Dispersal patterns of sandfish (Holothuria scabra) larvae in Manus Province, Papua New Guinea - Peter Waldie; David A. Feary; Michael Bode; Manuai Matawai; Hugo B. Harrison; Michael L. Berumen; Chris Molai; Maunoa Karo; Richard J. Hamilton (Frontiers in Marine Science, 2024)
In many tropical nations, coastal communities seek to manage their sea cucumber fisheries by establishing locally managed marine areas on their traditional fishing grounds. These managed areas can protect spawning stocks, however the extent to which they help to replenish nearby sea cucumber fisheries is debated, as nothing is known about the scales at which sea cucumber larvae disperse. In this study, we used genetic parentage analyses and statistical modelling to provide the first empirical measure of larval dispersal patterns for a sea cucumber species. We analysed tissue samples from 765 adult and 827 juvenile sandfish ( Holothuria scabra ) collected from five traditional fishing grounds of the Titan tribe, from Manus Province, Papua New Guinea. All adults were sampled from the Pere fishing grounds (the larval source area), with juveniles sampled from the Pere, Mbunai, Tawi, Timonai and Mbuke fishing grounds. Parentage analysis identified 15 juveniles that were the offspring of parents sampled from Pere fishing grounds, with six of these juveniles located in the same fishing grounds as their parents. The best-fit larval dispersal kernel predicted that the average H. scabra larvae travelled 15 km from its spawning location, with 50% of larvae settling within 6.7 km of their parents and 95% of larvae settling within 59 km of their parents. These results suggest that the Titan tribes’ desire to protect their H. scabra spawning stocks by establishing a network of locally managed marine areas across 65 km of continuous coastline is a culturally appropriate strategy, which has merit from both an ecological and fisheries standpoint.

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

A microbial risk assessor's guide to Valley Fever (Coccidioides spp.): Case study and review of risk factors - David Kahn; William Chen; Yarrow Linden; Karalee A. Corbeil; Sarah Lowry; Ciara A. Higham; Karla S. Mendez; Paige Burch; Taylor DiFondi; Marc Verhougstraete; Anneclaire J. De Roos; Charles N. Haas; et al. (Science of The Total Environment, 2024)

Reductive sorption of vanadium by iron monosulfide in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; Nicholas J.C. Doriean; David T. Welsh; Joseph A. Otte; Jessica Hamilton; Donald E. Canfield; Yun Wang; Enzo Lombi; William W. Bennett (Chemical Geology, 2024)

Synthetic asphaltene for green carbon material - Masato Morimoto; David E. Scott; Robin J. Hamilton; Jeffrey M. Stryker; Rik R. Tykwinski; Murray R. Gray (Fuel, 2024)

Evaluating a microalga (Schizochytrium sp.) as an alternative to fish oil in fish-free feeds for sablefish (Anoplopoma fimbria) - Katherine A. Neylan; Ronald B. Johnson; Frederic T. Barrows; David P. Marancik; Scott L. Hamilton; Luke D. Gardner (Aquaculture, 2024)

Response of streamflow and nutrient loads in a small temperate catchment subject to land use change - Gebiaw T. Ayele; Bofu Yu; Andy Bruere; David P. Hamilton (Environmental Monitoring and Assessment, 2023)
The aim of this study was to quantify the effect of land use change (LUC) implemented to meet nutrient load targets for a freshwater lake in New Zealand. We used the Soil and Water Assessment Tool (SWAT) model in combination with a non-parametric statistical test to determine whether afforestation of 15% of a subcatchment area was adequate to meet assigned nutrient load targets. A regional management authority set nutrient load targets of reduction in total nitrogen (TN) by 0.9 t yr −1 and reduction in total phosphorus (TP) by 0.05 t yr −1 to avoid eutrophication in the receiving waters of a freshwater lake. The load reduction was designed to be achieved through 200 ha of LUC from pasture to trees. Analysis of nutrient loads before, during, and following LUC shows that a 15% increase in forest cover decreased the annual flow (7.2%), TP load (33.3%), and TN load (13.1%). As flow and water quality observations were discrete and at irregular intervals, we used a parametric test and the SWAT model as different lines of evidence to demonstrate the effect of afforestation on flow and water quality. Policymakers concerned with decisions about LUC to improve the quality of receiving waters can benefit from applying our findings and using a statistical and numerical modelling framework to evaluate the adequacy of land use change to support improvements in water quality.

HARP: A suite of parameters to describe the hysteresis of streamflow and water quality constituents - Melanie E. Roberts; Donghwan Kim; Jing Lu; David P. Hamilton (Journal of Hydrology, 2023)

Impacts of climate change on nutrient and sediment loads from a subtropical catchment - Rohan Eccles; Hong Zhang; David Hamilton; Ralph Trancoso; Jozef Syktus (Journal of Environmental Management, 2023)

Reductive sorption of vanadium by green rust in seawater - Felicia J. Haase; Colton J. Vessey; Ryo Sekine; David Welsh; Jessica Hamilton; Yun Wang; Jessica White; Donald E. Canfield; Enzo Lombi; William W. Bennett (Geochimica et Cosmochimica Acta, 2023)

A slurry approach to identify nutrient critical source areas from subtropical catchment erosion - Jing Lu; Alexandra Garzon-Garcia; David P. Hamilton; Joanne Burton; Michele A. Burford (Journal of Environmental Management, 2023)

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

Effects of ocean acidification on dopamine-mediated behavioral responses of a coral reef damselfish - Trevor J. Hamilton; Martin Tresguerres; Garfield T. Kwan; Joshua Szaskiewicz; Brian Franczak; Tyler Cyronak; Andreas J. Andersson; David I. Kline (Science of The Total Environment, 2023)

Conventional loose mineral with added red clover leaf (Trifolium pratense L.) reverses vasoconstriction associated with tall fescue toxicosis in steers - Brittany E. Davis; Tracy A. Hamilton; John T. Johns; David L. Harmon; James L. Klotz; Jennifer R. Weinert-Nelson; Jack P. Goodman; John May; Huihua Ji; F. Neal Schrick; Michael D. Flythe (Animal Feed Science and Technology, 2023)

Methods to control harmful algal blooms: a review - Barathan Balaji-Prasath; Ying Wang; Yu Ping Su; David P. Hamilton; Hong Lin; Luwei Zheng; Yong Zhang (Environmental Chemistry Letters, 2022)

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Benefits and Challenges of a Stakeholder-Driven Shellfish Toxicity Forecast in Coastal Maine - Nicholas R. Record; Johnathan Evanilla; Kohl Kanwit; Craig Burnell; Carmen Cartisano; Bryant J. Lewis; Jill MacLeod; Benjamin Tupper; David W. Miller; Adrienne T. Tracy; Carol White; Matt Moretti; et al. (Frontiers in Marine Science, 2022)
Paralytic shellfish poison (PSP) is a human health concern for shellfish aquaculture and wild harvest. This paper discusses lessons learned from a forecasting program for PSP in coastal Maine, USA, designed based on stakeholder input, and run in an operational mode for the 2021 season. The forecast uses a deep learning algorithm to make site-specific, probabilistic forecasts at a weekly forecast range for toxin levels measured in shellfish tissue. Forecasts had high accuracy in the 2021 season, correctly predicting closure events and locations despite a highly unusual season. Stakeholders reported a positive view of the forecast system, and stakeholder input continues to be of key importance as further modifications are made to the system. There are benefits and challenges to the stakeholder-based design of the system.

Artificial intelligence for right whale photo identification: from data science competition to worldwide collaboration - Christin Khan; Drew Blount; Jason Parham; Jason Holmberg; Philip Hamilton; Claire Charlton; Fredrik Christiansen; David Johnston; Will Rayment; Steve Dawson; Els Vermeulen; Victoria Rowntree; et al. (Mammalian Biology, 2022)
Photo identification is an important tool in the conservation management of endangered species, and recent developments in artificial intelligence are revolutionizing existing workflows to identify individual animals. In 2015, the National Oceanic and Atmospheric Administration hosted a Kaggle data science competition to automate the identification of endangered North Atlantic right whales ( Eubalaena glacialis ). The winning algorithms developed by Deepsense.ai were able to identify individuals with 87% accuracy using a series of convolutional neural networks to identify the region of interest, create standardized photographs of uniform size and orientation, and then identify the correct individual. Since that time, we have brought in many more collaborators as we moved from prototype to production. Leveraging the existing infrastructure by Wild Me, the developers of Flukebook, we have created a web-based platform that allows biologists with no machine learning expertise to utilize semi-automated photo identification of right whales. New models were generated on an updated dataset using the winning Deepsense.ai algorithms. Given the morphological similarity between the North Atlantic right whale and closely related southern right whale ( Eubalaena australis ), we expanded the system to incorporate the largest long-term photo identification catalogs around the world including the United States, Canada, Australia, South Africa, Argentina, Brazil, and New Zealand. The system is now fully operational with multi-feature matching for both North Atlantic right whales and southern right whales from aerial photos of their heads (Deepsense), lateral photos of their heads (Pose Invariant Embeddings), flukes (CurvRank v2), and peduncle scarring (HotSpotter). We hope to encourage researchers to embrace both broad data collaborations and artificial intelligence to increase our understanding of wild populations and aid conservation efforts.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Restoring shallow lakes impaired by eutrophication: Approaches, outcomes, and challenges - Jonathan M. Abell; Deniz Özkundakci; David P. Hamilton; Paula Reeves (Critical Reviews in Environmental Science and Technology, 2022)

Cyanobacteria species dominance and diversity in three Australian drinking water reservoirs - Benny Zuse Rousso; Edoardo Bertone; Rodney A. Stewart; Sara P. Hughes; Peter Hobson; David P. Hamilton (Hydrobiologia, 2022)
The objective of this study was to identify correlations between environmental variables and cyanobacterial diversity, succession and dominance in three Australian water supply reservoirs. We assessed up to 15 years of in-lake water quality monitoring data from Lake Wivenhoe and Lake Tingalpa (Queensland), and Lake Myponga (South Australia). Lakes Wivenhoe and Tingalpa, subject to a subtropical climate, had higher cyanobacterial richness than Lake Myponga in temperate South Australia. Richness in the subtropical lakes was positively correlated ( P < 0.05) with total cyanobacteria biomass, and cyanobacteria biovolume > 0.03 mm 3 /l (Alert level 1; World Health Organization) was often composed of multiple cyanobacteria species. Peaks in total cyanobacteria biomass and diversity occurred in all three lakes from late spring to early autumn. Unicellular picocyanobacterial dominance was negatively correlated ( P < 0.05) with total nitrogen while dominance of colonial and filamentous species with larger cells (e.g. Microcystis spp., Raphidiopsis spp., Dolichospermum circinale ) was positively correlated ( P < 0.05) with total phosphorus. Among the species with larger cells, diazotrophic D. circinale often dominated when total nitrogen was at low concentrations. Our results support decision making for selecting cyanoHAB control strategies based on single- or multi-species dominance and reinforce that new monitoring technologies could support species-level assessments.

Can artificial light promote submerged macrophyte growth in summer? - Chao Xu; Hai-Jun Wang; Yan Li; Chi Xu; Qing Yu; Miao Liu; Miao Zhang; Hong-Zhu Wang; David P. Hamilton; Erik Jeppesen (Aquatic Ecology, 2022)

Venoms for all occasions: The functional toxin profiles of different anatomical regions in sea anemones are related to their ecological function - Lauren M. Ashwood; Eivind A. B. Undheim; Bruno Madio; Brett R. Hamilton; Marymegan Daly; David A. Hurwood; Glenn F. King; Peter J. Prentis (Molecular Ecology, 2022)
The phylum Cnidaria is the oldest extant venomous group and is defined by the presence of nematocysts, specialized organelles responsible for venom production and delivery. Although toxin peptides and the cells housing nematocysts are distributed across the entire animal, nematocyte and venom profiles have been shown to differ across morphological structures in actiniarians. In this study, we explore the relationship between patterns of toxin expression and the ecological roles of discrete anatomical structures in Telmatactis stephensoni . Specifically, using a combination of proteomic and transcriptomic approaches, we examined whether there is a direct correlation between the functional similarity of regions and the similarity of their associated toxin expression profiles. We report that the regionalization of toxin production is consistent with the partitioning of the ecological roles of venom across envenomating structures, and that three major functional regions are present in T . stephensoni : tentacles, epidermis and gastrodermis. Additionally, we find that most structures that serve similar functions not only have comparable putative toxin profiles but also similar nematocyst types. There was no overlap in the putative toxins identified using proteomics and transcriptomics, but the expression patterns of specific milked venom peptides were conserved across RNA‐sequencing and mass spectrometry imaging data sets. Furthermore, based on our data, it appears that acontia of T . stephensoni may be transcriptionally inactive and only mature nematocysts are present in the distal portions of the threads. Overall, we find that the venom profile of different anatomical regions in sea anemones varies according to its ecological functions.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Global co‐occurrence of methanogenic archaea and methanotrophic bacteria in Microcystis aggregates - Chuang Li; K. David Hambright; Hannah G. Bowen; Majoi A. Trammell; Hans‐Peter Grossart; Michele A. Burford; David P. Hamilton; Helong Jiang; Delphine Latour; Elisabeth I. Meyer; Judit Padisák; Richard M. Zamor; et al. (Environmental Microbiology, 2021)
Summary Global warming and eutrophication contribute to the worldwide increase in cyanobacterial blooms, and the level of cyanobacterial biomass is strongly associated with rises in methane emissions from surface lake waters. Hence, methane‐metabolizing microorganisms may be important for modulating carbon flow in cyanobacterial blooms. Here, we surveyed methanogenic and methanotrophic communities associated with floating Microcystis aggregates in 10 lakes spanning four continents, through sequencing of 16S rRNA and functional marker genes. Methanogenic archaea (mainly Methanoregula and Methanosaeta ) were detectable in 5 of the 10 lakes and constituted the majority (~50%–90%) of the archaeal community in these lakes. Three of the 10 lakes contained relatively more abundant methanotrophs than the other seven lakes, with the methanotrophic genera Methyloparacoccus , Crenothrix , and an uncultured species related to Methylobacter dominating and nearly exclusively found in each of those three lakes. These three are among the five lakes in which methanogens were observed. Operational taxonomic unit (OTU) richness and abundance of methanotrophs were strongly positively correlated with those of methanogens, suggesting that their activities may be coupled. These Microcystis ‐aggregate‐associated methanotrophs may be responsible for a hitherto overlooked sink for methane in surface freshwaters, and their co‐occurrence with methanogens sheds light on the methane cycle in cyanobacterial aggregates.

High contribution of methane in greenhouse gas emissions from a eutrophic lake: a mass balance synthesis - Arianto B. Santoso; David P. Hamilton; Louis A. Schipper; Ilia S. Ostrovsky; Chris H. Hendy (New Zealand Journal of Marine and Freshwater Research, 2021)
Lakes are ‘hotspots’ for greenhouse gas (GHG) emissions, primarily carbon dioxide (CO 2 ) and methane (CH 4 ). Understanding the processes regulating GHG emissions from lakes, and their temporal variability, is essential for more accurately quantifying the role of lakes in global GHG cycles. In this study, we identified the processes that affect CO 2 and CH 4 concentrations in a small (0.3 km 2 ) eutrophic monomictic lake (Okaro, New Zealand). A mass balance model was used to calculate changes in CO 2 and CH 4 storage in the lake as a result of internal cycling and atmospheric fluxes. To support model computations, CO 2 and CH 4 concentrations profiles were measured monthly over a one‐year period, in addition to temperature, dissolved oxygen and chlorophyll a . Annually, Lake Okaro acted as a sink of CO 2 from the atmosphere (425.4 mmol CO 2 m −2 y −1 ) and a source of CH 4 (553.4 mmol CH 4 m −2 y −1 ) equating to a net GHG emission (diffusive fluxes of CO 2 and CH 4 combined) of 0.22 kg CO 2 ‐eq m −2 y −1 . Although it may be viewed as conservative and applies only to diffusive fluxes, our study indicates that eutrophic lakes with high rates of primary production may act as a net source of GHGs.

Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread - Calum X. Cunningham; Sebastien Comte; Hamish McCallum; David G. Hamilton; Rodrigo Hamede; Andrew Storfer; Tracey Hollings; Manuel Ruiz‐Aravena; Douglas H. Kerlin; Barry W. Brook; Greg Hocking; Manna E. Jones (Ecology Letters, 2021)
Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance.

Alternative Biogeochemical States of River Pools Mediated by Hippo Use and Flow Variability - Christopher L. Dutton; Amanda L. Subalusky; Stephen K. Hamilton; Ella C. Bayer; Laban Njoroge; Emma J. Rosi; David M. Post (Ecosystems, 2021)

Reference and current Trophic Level Index of New Zealand lakes: benchmarks to inform lake management and assessment - Jonathan M. Abell; Paul van Dam‐Bates; Deniz Özkundakci; David P. Hamilton (New Zealand Journal of Marine and Freshwater Research, 2020)
Knowledge of trophic status is fundamental to understanding the condition and function of lake ecosystems. We developed regression models to predict chlorophyll a concentrations (chl a ) in New Zealand lakes for reference and current states, based on an existing dataset of total nitrogen (TN) and total phosphorus (TP) concentrations for 1031 lakes. Models were then developed to predict Secchi depth based on chl a and a sediment resuspension term applicable to shallow lakes. Estimates of all four Trophic Level Index (TLI) variables (chl a , TN, TP and Secchi depth) were analysed to estimate reference and current state TLI for the nationally representative sample of 1031 lakes. There was a trend of eutrophication between reference and current states, with systematic differences among lake geomorphic types. Mean chl a increased 3.5‐fold (2.42 mg m −3 vs. 8.32 mg m −3 ) and mean Secchi depth decreased (indicating lower clarity) by approximately one‐third (9.62 m vs. 6.48 m) between reference and current states. On average, TLI increased by 0.67, with the TLI increase >1 in approximately one‐third (31%) of lakes. This study informs the status of lake ecosystems in NZ and provides benchmarks to guide management and assessment.

Estimating cancer treatment intensity from SEER cancer registry data: methods and implications for population-based registry studies of pediatric cancers - Jessica L. Tobin; Stefanie M. Thomas; David R. Freyer; Ann S. Hamilton; Joel E. Milam (Cancer Causes & Control, 2020)

The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

Effects of hypoxia on the behavior and physiology of kelp forest fishes - Evan G. Mattiasen; Neosha S Kashef; David M. Stafford; Cheryl A. Logan; Susan M. Sogard; Eric P. Bjorkstedt; Scott L. Hamilton (Global Change Biology, 2020)
Forecasts from climate models and oceanographic observations indicate increasing deoxygenation in the global oceans and an elevated frequency and intensity of hypoxic events in the coastal zone, which have the potential to affect marine biodiversity and fisheries. Exposure to low dissolved oxygen (DO) conditions may have deleterious effects on early life stages in fishes. This study aims to identify thresholds to hypoxia while testing behavioral and physiological responses of two congeneric species of kelp forest fish to four DO levels, ranging from normoxic to hypoxic (8.7, 6.0, 4.1, and 2.2 mg O 2 /L). Behavioral tests identified changes in exploratory behavior and turning bias (lateralization), whereas physiological tests focused on determining changes in hypoxia tolerance (pCrit), ventilation rates, and metabolic rates, with impacts on the resulting capacity for aerobic activity. Our findings indicated that copper rockfish ( Sebastes caurinus ) and blue rockfish ( Sebastes mystinus ) express sensitivity to hypoxia; however, the strength of the response differed between species. Copper rockfish exhibited reduced absolute lateralization and increased escape time at the lowest DO levels, whereas behavioral metrics for blue rockfish did not vary with oxygen level. Both species exhibited decreases in aerobic scope (as a function of reduced maximum metabolic rate) and increases in ventilation rates to compensate for decreasing oxygen levels. Blue rockfish had a lower pCrit and stronger acclimation response compared to copper rockfish. The differences expressed by each species suggest that acclimatization to changing ocean conditions may vary, even among related species that recruit to the same kelp forest habitat, leading to winners and losers under future ocean conditions. Exposure to hypoxia can decrease individual physiological fitness through metabolic and aerobic depression and changes to anti‐predator behavior, with implications for the outcome of ecological interactions and the management of fish stocks in the face of climate change.

Multiple axes of ecological vulnerability to climate change - Matthew M. Kling; Stephanie L. Auer; Patrick J. Comer; David D. Ackerly; Healy Hamilton (Global Change Biology, 2020)
Observed ecological responses to climate change are highly individualistic across species and locations, and understanding the drivers of this variability is essential for management and conservation efforts. While it is clear that differences in exposure, sensitivity, and adaptive capacity all contribute to heterogeneity in climate change vulnerability, predicting these features at macroecological scales remains a critical challenge. We explore multiple drivers of heterogeneous vulnerability across the distributions of 96 vegetation types of the ecologically diverse western US, using data on observed climate trends from 1948 to 2014 to highlight emerging patterns of change. We ask three novel questions about factors potentially shaping vulnerability across the region: (a) How does sensitivity to different climate variables vary geographically and across vegetation classes? (b) How do multivariate climate exposure patterns interact with these sensitivities to shape vulnerability patterns? (c) How different are these vulnerability patterns according to three widely implemented vulnerability paradigms—niche novelty (decline in modeled suitability), temporal novelty (standardized anomaly), and spatial novelty (inbound climate velocity)—each of which uses a distinct frame of reference to quantify climate departure? We propose that considering these three novelty paradigms in combination could help improve our understanding and prediction of heterogeneous climate change responses, and we discuss the distinct climate adaptation strategies connected with different combinations of high and low novelty across the three metrics. Our results reveal a diverse mosaic of climate change vulnerability signatures across the region's plant communities. Each of the above factors contributes strongly to this heterogeneity: climate variable sensitivity exhibits clear patterns across vegetation types, multivariate climate change data reveal highly diverse exposure signatures across locations, and the three novelty paradigms diverge widely in their climate change vulnerability predictions. Together, these results shed light on potential drivers of individualistic climate change responses and may help to inform effective management strategies.

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Phycocyanin sensors as an early warning system for cyanobacteria blooms concentrations: a case study in the Rotorua lakes - Vanessa Cotterill; David P. Hamilton; Jonathan Puddick; Alastair Suren; Susanna A. Wood (New Zealand Journal of Marine and Freshwater Research, 2019)
Cyanobacterial blooms pose health risks to recreational water users. In New Zealand, cyanobacteria biovolumes are used to assess risk, but analyses can be time‐consuming and costly. In this study, measurements from a handheld phycocyanin sensor (Cyclops‐7, Turner Designs, USA) were compared with biovolumes from five lakes and a river in the Rotorua district over two years (2016, n = 121; 2017, n = 63). In the laboratory, relationships between sensor phycocyanin and biovolumes were assessed for four species to investigate precision and detection limits. The relationship between phycocyanin and biovolume was generally weak ( R 2 = 0.4) and varied among lakes and years, except at high biovolumes. Precision and detection limits differed among species. The biovolume detection limit derived from relationships with phycocyanin was above alert level thresholds for two of the four cyanobacteria species assessed. The phycocyanin sensor that was tested likely has limited utility but may be useful for on‐site confirmation of exceedances of alert level thresholds corresponding to when authorities should immediately issue health warnings.

Long‐term changes in the water quality of a deep temperate oligotrophic lake in response to catchment disturbance: evidence from sediment cores - Alfred Theodore N. K. Kpodonu; David P. Hamilton; Christopher H. Lusk; Adam Hartland; Daniel C. Laughlin; Piet Verburg (New Zealand Journal of Marine and Freshwater Research, 2019)
This study examined long‐term stability in water quality of Lake Okataina, North Island, New Zealand, inferred from sediments deposited from 1836 to 2009, during which time there was a pyroclastic volcanic eruption (Tarawera 1886) and successive introductions of invasive mammals. Multiple geochemical proxies were analysed stratigraphically for organic matter loading, primary productivity, redox potential and phosphorus retention capacity. Organic matter loading to the lake is mostly authochthonous (algae) although there was increased allochthonous (terrestrial) loading immediately after the Tarawera eruption. After 1920, there was a sustained increase in inorganic erosion flux. Primary productivity appeared to increase considerably about 1960, but has remained relatively unchanged more recently. Our results suggest that the lake could recover from the impact of the volcanic eruption within a few decades, but the introduction of mammals may affect its resilience and lead to more pervasive impacts on the biogeochemistry.

Tropical Coastal Wetlands Ameliorate Nitrogen Export During Floods - Maria Fernanda Adame; Melanie E. Roberts; David P. Hamilton; Christopher E. Ndehedehe; Vanessa Reis; Jing Lu; Matthew Griffiths; Graeme Curwen; Mike Ronan (Frontiers in Marine Science, 2019)

The Antarctic mite, Alaskozetes antarcticus, shares bacterial microbiome community membership but not abundance between adults and tritonymphs - Christopher J. Holmes; Emily C. Jennings; J. D. Gantz; Drew Spacht; Austin A. Spangler; David L. Denlinger; Richard E. Lee; Trinity L. Hamilton; Joshua B. Benoit (Polar Biology, 2019)

Diversity of anammox bacteria and abundance of functional genes for nitrogen cycling in the rhizosphere of submerged macrophytes in a freshwater lake in summer - Jianwei Zhao; Yangfan Xu; Lei Peng; Guanglong Liu; Xiaoqiong Wan; Yumei Hua; Duanwei Zhu; David P. Hamilton (Journal of Soils and Sediments, 2019)

A Quantitative Meta-analysis of Olfactory Dysfunction in Epilepsy - Kiran Khurshid; Andrew J. D. Crow; Petra E. Rupert; Nancy L. Minniti; Melissa A. Carswell; Dawn J. Mechanic-Hamilton; Vidyulata Kamath; Richard L. Doty; Paul J. Moberg; David R. Roalf (Neuropsychology Review, 2019)

The small-world topology of Clovis lithic networks - Briggs Buchanan; Marcus J. Hamilton; J. David Kilby (Archaeological and Anthropological Sciences, 2019)

Comparison of Unyvero P55 Pneumonia Cartridge, in-house PCR and culture for the identification of respiratory pathogens and antibiotic resistance in bronchoalveolar lavage fluids in the critical care setting - Naomi J. Gadsby; Martin P. McHugh; Callum Forbes; Laura MacKenzie; Stephen K. D. Hamilton; David M. Griffith; Kate E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Geographic and temporal variations in turbulent heat loss from lakes: A global analysis across 45 lakes - R. Iestyn Woolway; Piet Verburg; John D. Lenters; Christopher J. Merchant; David P. Hamilton; Justin Brookes; Elvira de Eyto; Sean Kelly; Nathan C. Healey; Simon Hook; Alo Laas; Don Pierson; et al. (Limnology and Oceanography, 2018)
Heat fluxes at the lake surface play an integral part in determining the energy budget and thermal structure in lakes, including regulating how lakes respond to climate change. We explore patterns in turbulent heat fluxes, which vary across temporal and spatial scales, using in situ high‐frequency monitoring data from 45 globally distributed lakes. Our analysis demonstrates that some of the lakes studied follow a marked seasonal cycle in their turbulent surface fluxes and that turbulent heat loss is highest in larger lakes and those situated at low latitude. The Bowen ratio, which is the ratio of mean sensible to mean latent heat fluxes, is smaller at low latitudes and, in turn, the relative contribution of evaporative to total turbulent heat loss increases toward the tropics. Latent heat transfer ranged from ~ 60% to > 90% of total turbulent heat loss in the examined lakes. The Bowen ratio ranged from 0.04 to 0.69 and correlated significantly with latitude. The relative contributions to total turbulent heat loss therefore differ among lakes, and these contributions are influenced greatly by lake location. Our findings have implications for understanding the role of lakes in the climate system, effects on the lake water balance, and temperature‐dependent processes in lakes.

Adaptation Design Tool for Climate-Smart Management of Coral Reefs and Other Natural Resources - Jordan M. West; Catherine A. Courtney; Anna T. Hamilton; Britt A. Parker; David A. Gibbs; Patricia Bradley; Susan H. Julius (Environmental Management, 2018)

Establishment of the exotic invasive Cuban treefrog (Osteopilus septentrionalis) in Louisiana - Brad M. Glorioso; James Hardin Waddle; Lindy J. Muse; Nicole D. Jennings; Melanie Litton; Joel Hamilton; Steven Gergen; David Heckard (Biological Invasions, 2018)

The role of mobile consumers in lake nutrient cycles: a brief review - Simon D. Stewart; David P. Hamilton; W. Troy Baisden; Piet Verburg; Ian C. Duggan (Hydrobiologia, 2018)

Diel behavior in moths and butterflies: a synthesis of data illuminates the evolution of temporal activity - Akito Y. Kawahara; David Plotkin; Chris A. Hamilton; Harlan Gough; Ryan St Laurent; Hannah L. Owens; Nicholas T. Homziak; Jesse R. Barber (Organisms Diversity & Evolution, 2018)

Constructed treatment wetlands provide habitat for zooplankton communities in agricultural peat lake catchments - Rebecca S. Eivers; Ian C. Duggan; David P. Hamilton; John M. Quinn (Wetlands, 2018)

Sensor manufacturer, temperature, and cyanobacteria morphology affect phycocyanin fluorescence measurements - Caroline M. Hodges; Susanna A. Wood; Jonathan Puddick; Christopher G. McBride; David P. Hamilton (Environmental Science and Pollution Research, 2018)

Left ventricular flow propagation velocity measurement: Is it cast in stone? - Bee Ting Chan; Hak Koon Yeoh; Yih Miin Liew; Yang Faridah Abdul Aziz; Ganiga Srinivasaiah Sridhar; Christian Hamilton-Craig; David Platts; Einly Lim (Medical & Biological Engineering & Computing, 2017)

Effects of selenium exposure on the hematology, innate immunity, and metabolic rate of yellow-bellied sliders (Trachemys scripta scripta) - David L. Haskins; Matthew T. Hamilton; Nicole I. Stacy; John W. Finger; Tracey D. Tuberville (Ecotoxicology, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Impacts of a bivalve mass mortality event on an estuarine food web and bivalve grazing pressure - Hannah F. E. Jones; Conrad A. Pilditch; David P. Hamilton; Karin R. Bryan (New Zealand Journal of Marine and Freshwater Research, 2017)
Declines in bivalve populations have been quite common worldwide, often associated with coastal development, pollution and climate change. In addition to the impacts of these chronic stressors, occasional mass mortality events may have severe consequences on ecosystem services and biodiversity. In this study, we examined the impact of a mass mortality event of the clam ( Austrovenus stutchburyi ) on an estuarine food web and the grazing pressure exerted by the bivalve population. In February 2009, c. 60% of the clam population died in Whangateau Harbour, New Zealand. Population clearance rate calculations suggest that the clam population do not exert significant top‐down control on phytoplankton biomass in the estuary, and thus the impact of the mortality event on bivalve grazing pressure was less severe than the reduction in abundance would suggest. A trophic model shows that phytoplankton play a limited role in the estuary food web, which is instead dominated by microphytobenthos and clams. This study highlights the importance of microphytobenthos in shallow estuaries, and the application of the trophic model is a useful tool that can identify key components of the ecosystem and could help inform monitoring programmes.

Carbon dioxide emissions and sediment organic carbon burials across a gradient of trophic state in eleven New Zealand lakes - Arianto B. Santoso; David P. Hamilton; Chris H. Hendy; Louis A. Schipper (Hydrobiologia, 2017)

Establishment and characterization of a platinum- and paclitaxel-resistant high grade serous ovarian carcinoma cell line - Pang-Ning Teng; Nicholas W. Bateman; Guisong Wang; Tracy Litzi; Brian E. Blanton; Brian L. Hood; Kelly A. Conrads; Wei Ao; Kate E. Oliver; Kathleen M. Darcy; William P. McGuire; Keren Paz; et al. (Human Cell, 2017)

The effect of prior knowledge of test endpoint on non-local muscle fatigue - Alan R. Hamilton; David G. Behm (European Journal of Applied Physiology, 2017)

Contrasting cyanobacterial communities and microcystin concentrations in summers with extreme weather events: insights into potential effects of climate change - Susanna A. Wood; Hugo Borges; Jonathan Puddick; Laura Biessy; Javier Atalah; Ian Hawes; Daniel R. Dietrich; David P. Hamilton (Hydrobiologia, 2017)

Predictive Models for Determination of E. coli Concentrations at Inland Recreational Beaches - Ayokunle Christopher Dada; David P. Hamilton (Water, Air, & Soil Pollution, 2016)

Mitigating harmful cyanobacterial blooms: strategies for control of nitrogen and phosphorus loads - David P. Hamilton; Nico Salmaso; Hans W. Paerl (Aquatic Ecology, 2016)

Modulation of microcystin congener abundance following nitrogen depletion of a Microcystis batch culture - Jonathan Puddick; Michèle R. Prinsep; Susanna A. Wood; S. Craig Cary; David P. Hamilton (Aquatic Ecology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

Spatial epidemiology of HIV-hepatitis co-infection in the State of Michigan: a cohort study - Zahid Butt; Sue Grady; Melinda Wilkins; Elizabeth Hamilton; David Todem; Joseph Gardiner; Mahdi Saeed (Infectious Diseases, 2015)

Empirical and semi-analytical chlorophyll a algorithms for multi-temporal monitoring of New Zealand lakes using Landsat - Mathew G. Allan; David P. Hamilton; Brendan Hicks; Lars Brabyn (Environmental Monitoring and Assessment, 2015)

Managing lateral infiltration on wide beds in clay and sandy clay loam using Hydrus 2D - Ghani Akbar; Steven Raine; Allen David McHugh; Greg Hamilton (Irrigation Science, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Ten ways remote sensing can contribute to conservation - Robert A. Rose; Dirck Byler; J. Ron Eastman; Erica Fleishman; Gary Geller; Scott Goetz; Liane Guild; Healy Hamilton; Matt Hansen; Rachel Headley; Jennifer Hewson; Ned Horning; et al. (Conservation Biology, 2015)
In an effort to increase conservation effectiveness through the use of Earth observation technologies, a group of remote sensing scientists affiliated with government and academic institutions and conservation organizations identified 10 questions in conservation for which the potential to be answered would be greatly increased by use of remotely sensed data and analyses of those data. Our goals were to increase conservation practitioners’ use of remote sensing to support their work, increase collaboration between the conservation science and remote sensing communities, identify and develop new and innovative uses of remote sensing for advancing conservation science, provide guidance to space agencies on how future satellite missions can support conservation science, and generate support from the public and private sector in the use of remote sensing data to address the 10 conservation questions. We identified a broad initial list of questions on the basis of an email chain‐referral survey. We then used a workshop‐based iterative and collaborative approach to whittle the list down to these final questions (which represent 10 major themes in conservation): How can global Earth observation data be used to model species distributions and abundances? How can remote sensing improve the understanding of animal movements? How can remotely sensed ecosystem variables be used to understand, monitor, and predict ecosystem response and resilience to multiple stressors? How can remote sensing be used to monitor the effects of climate on ecosystems? How can near real‐time ecosystem monitoring catalyze threat reduction, governance and regulation compliance, and resource management decisions? How can remote sensing inform configuration of protected area networks at spatial extents relevant to populations of target species and ecosystem services? How can remote sensing‐derived products be used to value and monitor changes in ecosystem services? How can remote sensing be used to monitor and evaluate the effectiveness of conservation efforts? How does the expansion and intensification of agriculture and aquaculture alter ecosystems and the services they provide? How can remote sensing be used to determine the degree to which ecosystems are being disturbed or degraded and the effects of these changes on species and ecosystem functions?

Phytoplankton succession and the formation of a deep chlorophyll maximum in a hypertrophic volcanic lake - Bernard Simmonds; Susanna A. Wood; Deniz Özkundakci; David P. Hamilton (Hydrobiologia, 2015)

Application of a Three-Dimensional Water Quality Model as a Decision Support Tool for the Management of Land-Use Changes in the Catchment of an Oligotrophic Lake - Dennis Trolle; Bob Spigel; David P. Hamilton; Ned Norton; Donna Sutherland; David Plew; Mathew G. Allan (Environmental Management, 2014)

Temporal and spatial trends in water quality of Lake Taihu, China: analysis from a north to mid-lake transect, 1991–2011 - Dilek Eren Akyuz; Liancong Luo; David P. Hamilton (Environmental Monitoring and Assessment, 2014)

Spatial and temporal patterns of carbon flow in a temperate, large river food web - Michael A. Pingram; Kevin J. Collier; David P. Hamilton; Brendan J. Hicks; Bruno O. David (Hydrobiologia, 2014)

Influence of Intra- and Interspecific Interactions on Short-term Movement of the Amphipod Corophium volutator in Varying Environmental Conditions - David Drolet; Michael R. S. Coffin; Myriam A. Barbeau; Diana J. Hamilton (Estuaries and Coasts, 2013)

Land Management Restrictions and Options for Change in Perpetual Conservation Easements - Adena Rissman; Menka Bihari; Christopher Hamilton; Christina Locke; David Lowenstein; Melissa Motew; Jessica Price; Robert Smail (Environmental Management, 2013)

Female American lobsters (Homarus americanus) do not delay their molt if they cannot find a mate - Susan L. Waddy; Natalie Hamilton-Gibson; David E. Aiken (Invertebrate Reproduction & Development, 2013)

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

A Male-Predominant Cuticular Hydrocarbon, 7-Methyltricosane, is used as a Contact Pheromone in the Western Flower Thrips Frankliniella occidentalis - Oladele A. Olaniran; Akella V. S. Sudhakar; Falko P. Drijfhout; Ian A. N. Dublon; David R. Hall; James G. C. Hamilton; William D. J. Kirk (Journal of Chemical Ecology, 2013)

Growth and turion formation of Potamogeton crispus in response to different phosphorus concentrations in water - Lei Wang; Tewu Yang; Duanwei Zhu; David Hamilton; Zhongnan Nie; Liangqing Liu; Xiaoqiong Wan; Congming Zhu (Aquatic Ecology, 2013)

Viability of Oryza sativa L. seeds stored under genebank conditions for up to 30 years - Fiona R. Hay; Flora de Guzman; David Ellis; Hazel Makahiya; Teresita Borromeo; N. Ruaraidh Sackville Hamilton (Genetic Resources and Crop Evolution, 2013)

Dispersal of marine benthic invertebrates through ice rafting - Colin B. A. Macfarlane; David Drolet; Myriam A. Barbeau; Diana J. Hamilton; Jeff Ollerhead (Ecology, 2013)
Knowledge of dispersal vectors used by organisms is essential to the understanding of population and community dynamics. We report on ice rafting, a vector by which intertidal benthic invertebrates can be transported well outside their normal dispersal range during winter in temperate climates. We found multiple invertebrate taxa in sediment‐laden ice blocks sampled in the intertidal zone. A large proportion of individuals were alive and active when freed from the ice. Using radio tracking, we found that ice blocks can travel over 20 km within a few days. Given the abundance of highly mobile ice blocks carrying viable invertebrates, we conclude that ice‐rafting is likely an important dispersal vector, contributing to spatial community dynamics in intertidal systems. This mechanism helps explain observed genetic structure of populations, but it also raises concerns about potential negative impacts of climate change on connectivity between populations.

A calcium-dependent interaction between calmodulin and the calponin homology domain of human IQGAP1 - William J. Andrews; Conor A. Bradley; Elaine Hamilton; Clare Daly; Thérèse Mallon; David J. Timson (Molecular and Cellular Biochemistry, 2012)

Catchment land use and trophic state impacts on phytoplankton composition: a case study from the Rotorua lakes’ district, New Zealand - Wendy J. Paul; David P. Hamilton; Ilia Ostrovsky; Steven D. Miller; Austin Zhang; Kohji Muraoka (Hydrobiologia, 2012)

Coupling high-resolution measurements to a three-dimensional lake model to assess the spatial and temporal dynamics of the cyanobacterium Planktothrix rubescens in a medium-sized lake - Elisa Carraro; Nicolas Guyennon; David Hamilton; Lucia Valsecchi; Emanuela C. Manfredi; Gaetano Viviano; Franco Salerno; Gianni Tartari; Diego Copetti (Hydrobiologia, 2012)

Putting the brakes on a cycle: bottom‐up effects damp cycle amplitude - James R. Bell; Eric C. Burkness; Alice E. Milne; David W. Onstad; Mark Abrahamson; Krista L. Hamilton; William D. Hutchison (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 310–318 Abstract Pest population density oscillations have a profound effect on agroecosystem functioning, particularly when pests cycle with epidemic persistence. Here, we ask whether landscape‐level manipulations can be used to restrict the cycle amplitude of the European corn borer moth [ Ostrinia nubilalis (Hübner)], an economically important maize pest. We analysed time series from Minnesota (1963–2009) and Wisconsin (1964–2009) to quantify the extent of regime change in the US Corn Belt where rates of transgenic Bt maize adoption varied. The introduction of Bt maize explained cycle damping when the adoption of the crop was high (Minnesota); oscillations were damped but continued to persist when Bt maize was used less intensely (Wisconsin). We conclude that host plant quality is key to understanding both epidemic persistence and the success of intervention strategies. In particular, the dichotomy in maize management between states is thought to limit the spatial autocorrelation of O. nubilalis .

A community-based framework for aquatic ecosystem models - Dennis Trolle; David P. Hamilton; Matthew R. Hipsey; Karsten Bolding; Jorn Bruggeman; Wolf M. Mooij; Jan H. Janse; Anders Nielsen; Erik Jeppesen; J. Alex Elliott; Vardit Makler-Pick; Thomas Petzoldt; et al. (Hydrobiologia, 2012)

Downscaling and visioning of mountain snow packs and other climate change implications in North Vancouver, British Columbia - Stewart Jay Cohen; Stephen Sheppard; Alison Shaw; David Flanders; Sarah Burch; Bill Taylor; David Hutchinson; Alex Cannon; Stuart Hamilton; Brent Burton; Jeff Carmichael (Mitigation and Adaptation Strategies for Global Change, 2012)

Denitrification Potential in Lake Sediment Increases Across a Gradient of Catchment Agriculture - Denise A. Bruesewitz; David P. Hamilton; Louis A. Schipper (Ecosystems, 2011)

The Role of Botanic Gardens in the Science and Practice of Ecological Restoration - KATE A. HARDWICK; PEGGY FIEDLER; LYNDON C. LEE; BRUCE PAVLIK; RICHARD J. HOBBS; JAMES ARONSON; MARTIN BIDARTONDO; ERIC BLACK; DAVID COATES; MATTHEW I. DAWS; KINGSLEY DIXON; STEPHEN ELLIOTT; et al. (Conservation Biology, 2011)
Many of the skills and resources associated with botanic gardens and arboreta, including plant taxonomy, horticulture, and seed bank management, are fundamental to ecological restoration efforts, yet few of the world's botanic gardens are involved in the science or practice of restoration. Thus, we examined the potential role of botanic gardens in these emerging fields. We believe a reorientation of certain existing institutional strengths, such as plant‐based research and knowledge transfer, would enable many more botanic gardens worldwide to provide effective science‐based support to restoration efforts. We recommend botanic gardens widen research to include ecosystems as well as species, increase involvement in practical restoration projects and training practitioners, and serve as information hubs for data archiving and exchange.

Rhizosphere interactions, carbon allocation, and nitrogen acquisition of two perennial North American grasses in response to defoliation and elevated atmospheric CO2 - David J. Augustine; Feike A. Dijkstra; E. William Hamilton III; Jack A. Morgan (Oecologia, 2011)

Hypolimnetic phosphorus and nitrogen dynamics in a small, eutrophic lake with a seasonally anoxic hypolimnion - Deniz Özkundakci; David P. Hamilton; Max M. Gibbs (Hydrobiologia, 2011)

Does sediment capping have post-application effects on zooplankton and phytoplankton? - Deniz Özkundakci; Ian C. Duggan; David P. Hamilton (Hydrobiologia, 2011)

Nitrogen and Phosphorus Limitation of Phytoplankton Growth in New Zealand Lakes: Implications for Eutrophication Control - Jonathan M. Abell; Deniz Özkundakci; David P. Hamilton (Ecosystems, 2010)

Stiffness and checking of Eucalyptus nitens sawn boards: genetic variation and potential for genetic improvement - David Blackburn; Matthew Hamilton; Chris Harwood; Trevor Innes; Brad Potts; Dean Williams (Tree Genetics & Genomes, 2010)

Temporal and spatial variations in phytoplankton productivity in surface waters of a warm-temperate, monomictic lake in New Zealand - Nina von Westernhagen; David P. Hamilton; Conrad A. Pilditch (Hydrobiologia, 2010)

Challenges and opportunities for integrating lake ecosystem modelling approaches - Wolf M. Mooij; Dennis Trolle; Erik Jeppesen; George Arhonditsis; Pavel V. Belolipetsky; Deonatus B. R. Chitamwebwa; Andrey G. Degermendzhy; Donald L. DeAngelis; Lisette N. De Senerpont Domis; Andrea S. Downing; J. Alex Elliott; Carlos Ruberto Fragoso; et al. (Aquatic Ecology, 2010)

Vertical distributions of chlorophyll in deep, warm monomictic lakes - David P. Hamilton; Katherine R. O’Brien; Michele A. Burford; Justin D. Brookes; Chris G. McBride (Aquatic Sciences, 2010)

The influence of water quality and sediment geochemistry on the horizontal and vertical distribution of phosphorus and nitrogen in sediments of a large, shallow lake - Dennis Trolle; Guangwei Zhu; David Hamilton; Liancong Luo; Chris McBride; Lu Zhang (Hydrobiologia, 2009)

Nutrient limitation of phytoplankton in solar salt ponds in Shark Bay, Western Australia - Richard D. Segal; Anya M. Waite; David P. Hamilton (Hydrobiologia, 2009)

Indoor/ambient residential air toxics results in rural western Montana - Tony J. Ward; Heidi Underberg; David Jones; Raymond F. Hamilton; Earle Adams (Environmental Monitoring and Assessment, 2009)

Conservation planning on a budget: a “resource light” method for mapping priorities at a landscape scale? - Karl A. Didier; David Wilkie; Iain Douglas-Hamilton; Laurence Frank; Nicholas Georgiadis; Max Graham; Festus Ihwagi; Anthony King; Alayne Cotterill; Dan Rubenstein; Rosie Woodroffe (Biodiversity and Conservation, 2009)

Pyric Herbivory: Rewilding Landscapes through the Recoupling of Fire and Grazing - SAMUEL D. FUHLENDORF; DAVID M. ENGLE; JAY KERBY; ROBERT HAMILTON (Conservation Biology, 2009)
Our understanding of fire and grazing is largely based on small‐scale experimental studies in which treatments are uniformly applied to experimental units that are considered homogenous. Any discussion of an interaction between fire and grazing is usually based on a statistical approach that ignores the spatial and temporal interactions on complex landscapes. We propose a new focus on the ecological interaction of fire and grazing in which each disturbance is spatially and temporally dependent on the other and results in a landscape where disturbance is best described as a shifting mosaic (a landscape with patches that vary with time since disturbance) that is critical to ecological structure and function of many ecosystems. We call this spatiotemporal interaction pyric herbivory (literal interpretation means grazing driven by fire). Pyric herbivory is the spatial and temporal interaction of fire and grazing, where positive and negative feedbacks promote a shifting pattern of disturbance across the landscape. We present data we collected from the Tallgrass Prairie Preserve in the southern Great Plains of North America that demonstrates that the interaction between free‐roaming bison ( Bison bison ) and random fires promotes heterogeneity and provides the foundation for biological diversity and ecosystem function of North American and African grasslands. This study is different from other studies of fire and grazing because the fires we examined were random and grazing animals were free to roam and select from burned and unburned patches. For ecosystems across the globe with a long history of fire and grazing, pyric herbivory with any grazing herbivore is likely more effective at restoring evolutionary disturbance patterns than a focus on restoring any large vertebrate while ignoring the interaction with fire and other disturbances .

Cooling lakes while the world warms: Effects of forest regrowth and increased dissolved organic matter on the thermal regime of a temperate, urban lake - Tanentzap Andrew J.; Yan Norman D.; Bill Keller; Robert Girard; Jocelyne Heneberry; John M. Gunn; David P. Hamilton; Peter A. Taylor (Limnology and Oceanography, 2008)
Depending on the magnitudes and directions of changes in air temperatures, winds, and underwater light attenuation, lakes may either warm or cool. Here we report a 28‐yr decrease in the whole‐lake average temperature of Clearwater Lake, Canada, despite regional signatures of climate warming. Using a one‐dimensional lake mixing model, we demonstrate that this pattern was attributable to a 35% reduction in surface wind speeds, itself explained by forest regrowth following local SO 2 emission reductions and tree planting, and a 10‐fold increase in dissolved organic carbon concentrations causing a substantial increase in vertical light attenuation following deacidification of the lake. Long‐term trends in lake temperatures do not necessarily follow those of air temperatures. The Clearwater Lake data demonstrate that any factors that influence local wind speeds and underwater light attenuation should be considered as modifiers of the effects of climate warming on lake thermal regimes.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Physiological responses induced by copper bioaccumulation in Eichhornia crassipes (Mart.) - Chaohua Hu; Lei Zhang; David Hamilton; Wenbing Zhou; Tewu Yang; Duanwei Zhu (Hydrobiologia, 2007)

Predicting tourism flows under climate change - Andrea Bigano; Jacqueline M. Hamilton; David J. Maddison; Richard S. J. Tol (Climatic Change, 2006)

Changes in markers of muscle damage, inflammation and HSP70 after an Ironman triathlon race - Katsuhiko Suzuki; Jonathan Peake; Kazunori Nosaka; Mitsuharu Okutsu; Chris R. Abbiss; Rob Surriano; David Bishop; Marc J. Quod; Hamilton Lee; David T. Martin; Paul B. Laursen (European Journal of Applied Physiology, 2006)

Venom yields from Australian and some other species of snakes - Peter J. Mirtschin; Nathan Dunstan; Ben Hough; Ewan Hamilton; Sharna Klein; Jonathan Lucas; David Millar; Frank Madaras; Timothy Nias (Ecotoxicology, 2006)

Annual basal area increment and growth duration of Pinus taeda in response to eight years of free‐air carbon dioxide enrichment - DAVID J. P. MOORE; SUSANNE AREF; RINGO M. HO; JEFFREY S. PIPPEN; JASON G. HAMILTON; EVAN H. DE LUCIA (Global Change Biology, 2006)
Rising CO 2 is predicted to increase forest productivity, although the duration of the response and how it might be altered by variation in rainfall, temperature and other environmental variables are not well understood. We measured the basal area of rapidly growing Pinus taeda trees exposed to free‐air CO 2 enrichment for 8 years and used these measurements to estimate monthly and annual growth. We used these measurements in a statistical model to estimate the start and end of growth in each year. Elevated CO 2 increased the basal area increment ( BAI ) of trees by 13–27%. In most years, exposure to elevated CO 2 increased the growth rate but not the duration of the active growth period. With the exception of 1 year following an extreme drought and a severe ice storm, BAI was positively correlated with the amount of rainfall during the active growth period. The interannual variation in the relative enhancement of BAI caused by elevated CO 2 was strongly related to temperature and rainfall, and was greatest in years with high vapor pressure deficit. There was no evidence of a systematic reduction in the stimulation of growth during the first 8 years of this experiment, suggesting that the hypothesized limitation of the CO 2 response caused by nitrogen availability has yet to occur.

Transition from Planktonic to Benthic Algal Dominance Along a Salinity Gradient - Richard D. Segal; Anya M. Waite; David P. Hamilton (Hydrobiologia, 2006)

Temporal Changes between Ecological Regimes in a Range of Primary and Secondary Salinised Wetlands - Karin Strehlow; Jenny Davis; Lien Sim; Jane Chambers; Stuart Halse; David Hamilton; Pierre Horwitz; Arthur McComb; Ray Froend (Hydrobiologia, 2005)

Identification of a Male-produced Aggregation Pheromone in the Western Flower Thrips Frankliniella occidentalis - James G. C. Hamilton; David R. Hall; William D. J. Kirk (Journal of Chemical Ecology, 2005)

Complex interactions between the zebra mussel, Dreissena polymorpha , and the harmful phytoplankter, Microcystis aeruginosa - Orlando Sarnelle; Alan E. Wilson; Stephen K. Hamilton; Lesley B. Knoll; David F. Raikow (Limnology and Oceanography, 2005)
We report a reversal in the sign of the herbivore‐phytoplankton interaction between the zebra mussel ( Dreissena polymorpha ) and Microcystis aeruginosa , a harmful planktonic cyanobacterium. A pair of large‐scale manipulations of mussel density in the same lake in consecutive years showed that when phosphorus concentrations were very low (mean total phosphorus [TP] ~ 3 µg L −1 ), the effect of Dreissena on the biomass of M. aeruginosa was monotonically negative across the full range of sustainable mussel densities. When the enclosures were fertilized with phosphorus (mean TP ~ 9 µg L −1 ), there was a monotonically positive effect of Dreissena on M. aeruginosa across the same mussel gradient. These contrasting results indicate that D. polymorpha feeds on M. aeruginosa , as shown in previous laboratory feeding experiments, but that the positive effects of D. polymorpha on M. aeruginosa can be larger than the negative effects of consumption. A sign reversal in the interaction between these two species is congruent with highly variable patterns in the response of M. aeruginosa to D. polymorpha invasion across lake and river systems in North America.

Large cooperativity in the removal of iron from transferrin at physiological temperature and chloride ion concentration - David H. Hamilton; Isabelle Turcot; Alain Stintzi; Kenneth N. Raymond (JBIC Journal of Biological Inorganic Chemistry, 2004)

Disaggregation of Microcystis aeruginosa colonies under turbulent mixing: laboratory experiments in a grid-stirred tank - Katherine R. O’Brien; David L. Meyer; Anya M. Waite; Gregory N. Ivey; David P. Hamilton (Hydrobiologia, 2004)

Alteration in Fluid Mechanics in Porcine Femoral Arteries with Atheroma Development - Yutong Liu; Andrew Hamilton; Ashwin Nagaraj; LiJing L. Yan; Kiang Liu; Yong-Gen Lai; David D. McPherson; Krishnan B. Chandran (Annals of Biomedical Engineering, 2004)

Dominance of the noxious cyanobacterium Microcystis aeruginosa in low‐nutrient lakes is associated with exotic zebra mussels - David F. Raikow; Orlando Sarnelle; Alan E. Wilson; Stephen K. Hamilton (Limnology and Oceanography, 2004)
To examine the hypothesis that invasion by zebra mussels ( Dreissena polymorpha ) promotes phytoplankton dominance by the noxious cyanobacterium Microcystis aeruginosa , 61 Michigan lakes of varying nutrient levels that contain or lack zebra mussels were surveyed during late summer. After accounting for variation in total phosphorus (TP) concentrations, lakes with Dreissena had lower total phytoplankton biomass, as measured by chlorophyll a and algal cell biovolume. Phytoplankton biomass increased with TP in both sets of lakes, although the elevations of the relationship differed. The percentage of the total phytoplankton comprised by cyanobacteria increased with TP in lakes without Dreissena (R 2 = 0.21, P = 0.025) but not in lakes with Dreissena (P = 0.79). Surprisingly, there was a positive influence of Dreissena invasion on Microcystis dominance in lakes with TP ≪ 25 µg L −1 (P 5 0.0018) but not in lakes with TP ≫ 25 µg L −1 (P = 0.86). The finding that Microcystis , a relatively grazing‐resistant component of the phytoplankton, was favored by Dreissena in low‐ but not in high‐nutrient lakes is somewhat counterintuitive, but predator‐prey models make this prediction in certain cases when the cost for the prey of being consumption resistant is a low maximum population growth rate. This Dreissena ‐cyanobacteria interaction contradicts well‐established patterns of increasing cyanobacteria with nutrient enrichment in north‐temperate lakes and suggests that the monitoring and abatement of nutrient inputs to lakes may not be sufficient to predict and control cyanobacterial dominance of Dreissena‐invaded lakes.

Simple mixing criteria for the growth of negatively buoyant phytoplankton - Katherine R. O'Brien; Gregory N. Ivey; David P. Hamilton; Anya M. Waite; Petra M. Visser (Limnology and Oceanography, 2003)
Phytoplankton population dynamics are controlled by the relative rather than absolute timescales of mixing, growth, and loss processes such as sedimentation, grazing, and so on. Here, the vertical distribution and biomass of phytoplankton populations are quantified by two timescale ratios: the Peclet number Pe—the ratio of mixing and sedimentation timescales—and the growth number G—the ratio of sedimentation and net growth timescales. Three mixing regimes are defined for phytoplankton and other particles. For Pe ≥ 100, the population is translated linearly down the water column over time and will leave the surface mixing layer completely after sedimentation timeτt s . For 0.1 c =— s /(G —1). This analysis is valid for negatively buoyant phytoplankton, except when mixing time is much longer than growth time and Pe≤ 0.1, which can occur for very slow sinking species. These regimes can be used for assessing the effect of changes in the mixing, growth, or sedimentation conditions on population dynamics. Published data from a lake and diurnally stratified river weir pool are used here to verify a minimum thermocline depth hypothesis proposed by others. Mixing and growth regimes are used to calculate minimum mixing depth h min and to determine phytoplankton sinking rates from published sediment trap data.

Variation between and within Trifolium repens L. populations collected from sown swards in Uruguay - Fernando Olmos; David Wilman; Ruaraidh Sackville Hamilton (Euphytica, 2003)

Quantitative trait loci (QTL) for lean body mass and body length in MRL/MPJ and SJL/J F 2 mice - Godfred Masinde; Xinmin Li; Weikuan Gu; Heather Davidson; Melanie Hamilton-Ulland; Jon Wergedal; Subburaman Mohan; David Baylink (Functional & Integrative Genomics, 2002)

Quantitative trait loci that harbor genes regulating muscle size in (MRL/MPJ × SJL/J) F 2 mice - Godfred Masinde; Xinmin Li; Weikuan Gu; Melanie Hamilton-Ulland; Subburaman Mohan; David Baylink (Functional & Integrative Genomics, 2002)

Physical and chemical limnology of 204 lakes from the Canadian Arctic Archipelago - Paul B. Hamilton; Konrad Gajewski; David E. Atkinson; David R.S. Lean (Hydrobiologia, 2001)

Bivalve diets in a midwestern U.S. stream: A stable isotope enrichment study - David F. Raikow; Stephen K. Hamilton (Limnology and Oceanography, 2001)
This study examined a community of stream bivalves (unionids and fingernail clams) in a second‐order woodland stream in southern Michigan using both the natural abundance of 15 N and a 6‐week whole‐stream 15 N enrichment experiment, as part of the Lotic Intersite Nitrogen eXperiment (LINX). Objectives included addressing what made up the diet of these bivalves and whether suspended algae consumed by bivalves were derived from pelagic phytoplankton imported from an upstream lake or attached algae sloughed from instream surfaces. Within the examination of bivalve diets, we considered whether suspension‐ and/or deposit‐feeding modes were employed and whether bivalves selectively assimilated the algal and microbial portions of bulk material they ingested. All 12 unionid species reached a level of 15 N enrichment greater than the bulk suspended organic matter. Sphaerium striatinum (Sphaeriidae) were enriched to levels greater than all presumed food sources. Suspended algae were derived both from sloughed epilithon and pelagic phytoplankton originating from lentic waters upstream. A mixing model suggested that unionids were consuming 80% deposited and 20% suspended material. Alternatively, these bivalves were preferentially assimilating the highly enriched living component of suspended and/or benthic organic matter rather than assimilating the bulk material. These results advance our understanding of freshwater bivalve‐feeding ecology, which is necessary if conservation efforts of these increasingly threatened organisms are to succeed.

Simulation of vertical position of buoyancy regulating Microcystis aeruginosa in a shallow eutrophic lake - Brett B. Wallace; Mark C. Bailey; David P. Hamilton (Aquatic Sciences, 2000)

Comparative toxicity of trivalent and pentavalent inorganic and methylated arsenicals in rat and human cells - Miroslav Styblo; Luz M. Del Razo; Libia Vega; Dori R. Germolec; Edward L. LeCluyse; Geraldine A. Hamilton; William Reed; Changqing Wang; William R. Cullen; David J. Thomas (Archives of Toxicology, 2000)

The red alga Asparagopsis taxiformis\Falkenbergia hillebrandii–a possible source of trichloroethylene and perchloroethylene? - Rhoda A. Marshall; John T. G. Hamilton; Matthew J. Dring; David B. Harper (Limnology and Oceanography, 2000)

Heritability of thrips resistance in the ‘IPA-3’ onion cultivar in South Texas - Brian K. Hamilton; Leonard M. Pike; Alton N. Sparks; David A. Bender; Richard W. Jones; Jonas Candeia; Geraldo de Franca (Euphytica, 1999)

The effect of variations in irradiance on buoyancy regulation in Microcystis aeruginosa - Brett B. Wallace; David P. Hamilton (Limnology and Oceanography, 1999)
A mechanism of buoyancy regulation in cyanobacteria was investigated in a fluctuating light environment typical of the mixed layer in a lake. New measurements of density and cellular carbohydrate content were obtained from a field sample of the cyanobacterium Microcystis aeruginosa . The rate of increase in carbohydrate and density in this cyanobacterium does not instantaneously adjust to an increase in light intensity. There is a time lag, the response time, corresponding to physiological adjustment to the increase in light, before equilibration of the rate of carbohydrate and density increase. Also, the rate of density and carbohydrate increase is nonlinear over the response time. Based on these experimental findings, a new model for buoyancy regulation was developed that includes the response time. This model was applied to two fluctuating light regimes that simulate Langmuir circulation and turbulence. The simulations reveal that the response time is critical in determining if a cell equilibrates its rate of density change to a change in the light that it receives. If the response time is longer than the time scale of the light fluctuation, then the rate of density increase will be less than the optimal equilibrium rate. Models that do not include the response time will not correctly predict the buoyancy of cyanobacteria and their water column position after an episode of mixing.

A comparative study of the backbone dynamics of two closely related lipid binding proteins: Bovine heart fatty acid binding protein and porcine ileal lipid binding protein - Christian Lücke; David Fushman; Christian Ludwig; James A. Hamilton; James C. Sacchettini; Heinz Rüterjans (Molecular and Cellular Biochemistry, 1999)

Vegetation dynamics in central Africa since 18,000 yr BP: pollen records from the interlacustrine highlands of Burundi, Rwanda and western Uganda - Dominique Jolly; David Taylor; Robert Marchant; Alan Hamilton; Raymonde Bonnefille; Guillaume Buchet; Guy Riollet (Journal of Biogeography, 1997)
A standardized analysis of palaeoecological data, in the form of six pollen sequences and forty‐ four radiocarbon ages, has permitted a region‐wide reconstruction of Late Quaternary vegetation dynamics for the interlacustrine highlands of central Africa. A landscape widely dominated by ericaceous scrub and grasslands, but also supporting sparse patches of open‐canopied montane forest, possibly in those areas with a topography most favourable to the growth of trees, is indicated for the last glacial maximum of 18,000 yr bp . Major expansions in the extent of upper altitudinal forms of montane forest occurred from around 12,500 yr bp , while lower moist montane forest—the expected climax for much of the region today—did not become prominent until 11,000 yr bp to 10,000 yr bp . From the palaeoecological evidence at least, it appears that the major east Central forest refuge, proposed by some workers on the basis of current species’ distribution patterns, did not extend to the eastern flanks of the Albertine Rift. A late glacial–early Holocene transition is only fully chronicled in two of the sites. However, it appears that the expansion of lower montane forest had a time‐transgressive pattern across the region, and was not simply from low to high altitude. The composition of forests during the early Holocene appears to have been different to that in the later stages of the present interglacial, as taxa presently associated with wetter and/or more open forest types were much more common. Pollen data also indicate that higher altitude parts of the interlacustrine highlands were more attractive to the earliest (possibly Bantu‐speaking) farmers and metal‐workers. There is evidence of wide‐spread forest clearance around the beginning of the present millennium, possibly as a result of substantial changes in socio‐economic conditions, and patterns of settlement, associated with the onset of the Late Iron Age.